Matematyka
Adrian145
2017-06-24 23:26:59
Rozwiąż równanie . Zad w zalaczniku
Odpowiedź
asia12319
2017-06-25 01:55:41

10,5+(√3/3)²-1/3*(1 1/2)³:(-5/12)= 10,5+3/9-1/3*(3/2)³:(-5/12)= 10 1/2+3/9-1/3*27/8*(-12/5)= 10 9/18+6/18-9/8*(-12/5)= 10 15/18+27/10= 10 75/90 + 2 63/90= 12 138/90=13 48/90=13 24/45= 13 8/15

ChInCyK1804
2017-06-25 01:56:56

[latex]10,5+( frac{ sqrt{3} }{3} ) ^{2} - frac{1}{3} *(1 frac{1}{2} ) ^{3} :(- frac{5}{12} )=10 frac{1}{2}+ frac{3}{9} - frac{1}{3} *( frac{3}{2} ) ^{3} :(- frac{5}{12} )= \ \ =10 frac{1}{2} + frac{1}{3} - frac{1}{3} * frac{27}{8} :(- frac{5}{12} )=10 frac{1}{2} + frac{1}{3} - frac{9}{8} *(- frac{12}{5} )= \ \ =10 frac{1}{2} + frac{1}{3} + frac{27}{10} =10 frac{1}{2}+ frac{1}{3} +2 frac{7}{10} =10 frac{15}{30} + frac{10}{30} +2 frac{21}{30} = [/latex] [latex]=12 frac{46}{30} =12 frac{23}{15} =13 frac{8}{15} [/latex]

Dodaj swoją odpowiedź